2021
DOI: 10.1038/s41415-021-3405-1
|View full text |Cite
|
Sign up to set email alerts
|

The future of dentistry post-COVID-19: perspectives from Urgent Dental Care centre staff in England

Abstract: Introduction While routine dentistry was suspended during the COVID-19 pandemic, Urgent Dental Care centres (UDCs) were established to support patients with urgent dental needs. Aim The study aimed to provide insights and recommendations on future dental reform based on the perspectives of frontline staff delivering dental care in UDCs. Method A qualitative research study using a phenomenological approach. A hybrid approach that incorporated both a ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…These procedures such as checking body temperature, reducing exposure of the patients and period in the dental clinic, efficient surfaces’ cleaning with H 2 O, and 1% NaCl following every patient. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…These procedures such as checking body temperature, reducing exposure of the patients and period in the dental clinic, efficient surfaces’ cleaning with H 2 O, and 1% NaCl following every patient. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 Chisini et al 28 conducted a study in the public national systems in Brazil, and showed a 89% decrease in children's dental practice in April 2020, a peak of the pandemic. Witton et al 29 conducted a qualitative research study in England to identify dental reforms post-pandemic, and reported that children's oral health was harmed due to the suspension of elective treatments. Therefore, the researchers recommended the creation of child oral health programs post-pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The negative economic impact of the pandemic on dental practice was visible and present after 2.5 years from its beginning, through a significant increase in the cost of expenses, and on the other hand, working with the same or fewer number of patients at the same or slightly increased service prices. In a study assessing the dentists’ attitudes toward the impact of the pandemic on dental practice in England, participants from public sector expressed concern about difficult patient access and the subsequent backlog of emergency cases, while those in private sector expressed concerns about practice sustainability [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%